PRÁTICAS LETRADAS NO VESTIBULAR: ANÁLISE DE UMA PROVA DE REDAÇÃO - Araújo, Denise Lino De (Intercâmbio, 2010)
This work on literacy and textual genre has the following objectives: (1) to describe the literacy practice required by the composition question of the college entrance examination held at the Federal University of Campina Grande (UFCG) in 2005, and (2) to point out the literacy practice used in order to answer that question. The results show dissociation between the literacy practice required by the examination and the one presented by candidates.